2019
DOI: 10.5603/gp.2019.0059
|View full text |Cite
|
Sign up to set email alerts
|

Skin markers and the prediction of intraabdominal adhesion during second Cesarean delivery

Abstract: Objectives: The aim of the present study has been to examine skin scar characteristics and striae gravidarum, considering the reliability of each for predicting adhesions in repeat Caesarean sections. Material and methods: A cross-sectional study was done over a period of two years. One hundred pregnant women were invited to participate in the study. Preoperatively, abdominal scar features (according to the scar's appearance) and stria gravidarum were both recorded. Then, at the time of surgery, intraabdominal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…In contention with the current study, there was no difference in peritoneal adhesions in women with or without striae (14,15). However, another study reported higher rates of intraperitoneal adhesions in women with no or mild striae than those with severe striae (67.3%, 65.9%, and 36.3%, respectively) (13).…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…In contention with the current study, there was no difference in peritoneal adhesions in women with or without striae (14,15). However, another study reported higher rates of intraperitoneal adhesions in women with no or mild striae than those with severe striae (67.3%, 65.9%, and 36.3%, respectively) (13).…”
Section: Discussioncontrasting
confidence: 48%
“…This was thought to arise from variability in transforming growth factor-beta, which plays an essential role in the formation of hypertrophic scars as well as intraperitoneal adhesions (13). Scar width and appearance showed signi cant association with dense intraperitoneal adhesions (p-value 0.001, and 0.002 respectively) (15). Depressed hypopigmented scars were also associated with adhesions, which were assumed to arise from the inward traction from the adhesion bands (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The results were not uniform; different markers such as a depressed or elevated scar, hyperpigmentation or hypopigmentation of the scar, scar width or scar lengths were all found to be predictive of adhesions in distinct studies. [5][6][7][8] These different results might be due to the fact that peritoneal healing starts all over the damaged surface as opposed to skin, which heals from the edges. 22 In 2017, a meta-analysis of the observational studies revealed that only depressed scars were statistically associated with intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Evaluation of the previous cesarean scar features (flat, depressed, elevated), scar pigmentation (non-pigmentation, hyperpigmentation), scar width and scar length have yielded conflicting results. [5][6][7][8] The absence of the free movement of the uterine anterior wall against the abdominal wall (sliding sign) on ultrasound is another sign of adhesions. 9,10 However, the interpretation of this technique needs experience to reach a high rate of intra-observer and inter-observer reproducibility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation